Peran Pemasaran Digital Dalam Pengembangan Pariwisata Kota Metro - Agnes Jevi Rialita; Amantun Nisfah Khoirun Nikmah; Nur Aeni (Journal on Education, 2024)
This study aims to examine the role of digital marketing in increasing visitor interest in tourism in Metro City. The background of this research is driven by the importance of using digital platforms in the tourism industry to promote tourist destinations. The research method used is a library research approach, analyzing various literature sources related to digital marketing and tourism. The findings indicate that social media and digital applications play a significant role in attracting visitors' interest and enhancing the visibility of tourist destinations. However, tourism managers in Metro City face the challenge of limited human resources with expertise in digital marketing. The implications of this study highlight the importance of improving human resource capacity and fostering collaboration between tourism managers and various stakeholders to optimize digital marketing efforts. Thus, well-structured digital marketing can increase the appeal of tourism and expand audience reach.